Anlotinib combined with transarterial chemoembolization for unresectable hepatocellular carcinoma associated with hepatitis B virus: a retrospective controlled study - Chen, Song; Cai, Hongjie; Wu, Zhiqiang; Tang, Shuangyan; Chen, Ludan; Wang, Fan; Zhuang, Wenquan; Guo, Wenbo (Frontiers in Oncology, 2023)
Purpose To investigate the efficacy and safety of combined treatment with anlotinib and transarterial chemoembolization (TACE) in patients with unresectable hepatocellular carcinoma (uHCC) associated with hepatitis B virus.We retrospectively collected the data of 96 uHCC patients associated with hepatitis B virus who received either TACE only (TO group; n=64) or anlotinib combined with TACE (TA group; n=32) between January 2017 to January 2021. The differences in overall survival (OS), progression-free survival (PFS), and tumor response according to mRECIST and RECIST 1.1 were compared between the two groups. Adverse events (AEs) were analyzed to assess the safety profiles.The mOS and mPFS were significantly higher in the TA group than that in the TO group (17.6 months vs. 9.4 months, p=0.018; 6.7 months vs. 3.8months, p=0.003; respectively). Additionally, the overall objective response rate (ORR) and disease control rate (DCR) numerically increased in the TA group (mRECIST: ORR 65.6% vs. 46. 9%, p=0.064; DCR 90.6% vs. 85.9%, p=0.382. RECIST 1.1: ORR 46.9% vs. 15.6%, p=0.001; DCR 90.6% vs. 85.9%, p=0.382; respectively). No treatment-related mortality occurred. The most common AEs included elevated transaminases (56.3%), decreased appetite (46.9%) and abdominal pain (37.5%) in TA group. Though the incidence rate of grade 3/4 was higher in TA group, all of them were controllable.Conclusions Anlotinib combined with TACE may significantly improve outcomes for uHCC patients associated with hepatitis B virus comparing with TACE monotherapy with a controllable safety profile. Randomized controlled trials with a large sample are warranted to further validate the efficacy.